Knockdown resistance mutations distribution and characteristics of Aedes albopictus field populations within eleven dengue local epidemic provinces in China - Zhao, Chunchun; Zhou, Xinxin; Xue, Chuizhao; Lun, Xinchang; Li, Wenyu; Liu, Xiaobo; Wu, Haixia; Song, Xiuping; Wang, Jun; Liu, Qiyong; Meng, Fengxia (Frontiers in Cellular and Infection Microbiology, 2023)
Aedes albopictus has produced magnificent resistance to most of insecticides especially pyrethroid which makes it is harder to prevent and control dengue fever due to absence of effective therapy and vaccine. Many scholars have proved that the target site of pyrethroids is the voltage-gated sodium channel gene (VGSC) whose mutation causes knockdown resistance (kdr). The spatial dis-tribution for kdr mutations in Ae. albopictus should be comprehensively analyze nationwide and the correlation between the kdr mutation and dengue fever need to be explored. In this study, a total of 2241 Ae. albopictus samples from 49 populations at 2020 form 11 provinces of mainland China were detected and analyzed for mutations in the VGSC gene. The overall frequencies of mutant alleles V1016, I1532 and F1534 were 13.19%, 4.89% and 46.90%, respectively. For V1016 and I1532, only one allele was detected which was GGA(G) and ACC(T), respectively. Five mutant alleles were found at codon 1534, namely TCC/S (33.49%), TGC/C (11.96%), TTG/L (0.60%), CTC/L (0.49%) and TTA/L (0.58%). Totally 31 types of triple-locus genotype combinations were found and the single locus mutation was most common. The 1016 and 1532 mutation rates were significantly negatively related to AAT but the 1534 mutation rate was significantly positively related to AAT. The 1532 mutation rate was significantly positively related to 1016 mutation rate but negatively related to 1534 mutation rate. Furthermore, spatial autocorrelation analysis showed spatial aggregation and positive spatial correlation. Therefore, the kdr mutation of Ae. albopictus is gradually becoming more complex. The mechanism of 1016 and 1532 mutation may be similar because of their positive cor-relation. On the other word, the characteristic of spatial aggregation of VGSC gene mutant rates in different areas should be took more attention.